Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.ccell.2016.04.013
|View full text |Cite|
|
Sign up to set email alerts
|

Compounds Triggering ER Stress Exert Anti-Melanoma Effects and Overcome BRAF Inhibitor Resistance

Abstract: We have discovered and developed a series of molecules (thiazole benzenesulfonamides). HA15, the lead compound of this series, displayed anti-cancerous activity on all melanoma cells tested, including cells isolated from patients and cells that developed resistance to BRAF inhibitors. Our molecule displayed activity against other liquid and solid tumors. HA15 also exhibited strong efficacy in xenograft mouse models with melanoma cells either sensitive or resistant to BRAF inhibitors. Transcriptomic, proteomic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
171
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(186 citation statements)
references
References 44 publications
(49 reference statements)
9
171
1
1
Order By: Relevance
“…These data support the biological relevance of the target, but further studies are needed to explore dose and regimen before this pharmacological agent can be translated into human adjuvant trials that target metastatic progression. It would be worthwhile to assess whether other GRP78-targeting chemical compounds such as HA15 [34] and medicarpin [35] have antimetastatic effects. Bioconjugates such as Mab159 [36] and BMTP78 [37] that target GRP78 have been shown to have antimetastatic effects.…”
Section: Discussionmentioning
confidence: 99%
“…These data support the biological relevance of the target, but further studies are needed to explore dose and regimen before this pharmacological agent can be translated into human adjuvant trials that target metastatic progression. It would be worthwhile to assess whether other GRP78-targeting chemical compounds such as HA15 [34] and medicarpin [35] have antimetastatic effects. Bioconjugates such as Mab159 [36] and BMTP78 [37] that target GRP78 have been shown to have antimetastatic effects.…”
Section: Discussionmentioning
confidence: 99%
“…ER stress-induced autophagy can also be highly cytotoxic, as was recently shown with the BiP inhibitor HA15. This compound induced apoptosis in a variety of chemoresistant cancer cell lines in vitro and in vivo , though the mechanism remains incompletely understood (Cerezo et al, 2016). In sum, optimal cancer growth and survival relies on carefully balanced UPR signaling pathways that interact with other cell processes such as autophagy, to result in cancer cell death or survival.…”
Section: Mechanisms Of Er Stress-mediated Tumor Progressionmentioning
confidence: 99%
“…Furthermore, in certain tumors such as melanoma, the most effective strategy for exploiting ER stress would most likely involve the combination of agents that inhibit cytoprotective function of UPR arms along with those that actively induce ER stress/response (64)(64). The second approach is to pharmacologically increase ER stress above a certain threshold in cells that already have a high dependency on the UPR, thereby triggering cell death (65). For instance, Cerezo et al reported the development of the small molecule HA15 belonging to the thiazole benzensulfonamides.…”
Section: The Upr Presents Multiple Potential Drug Targetsmentioning
confidence: 99%